PENGARUH GENANGAN PADA BEBERAPA FASE PERTUMBUHAN TERHADAP FOTOSINTESIS DAN HASIL EMPAT KULTIVAR JAGUNG (Zea mays L.) - , PUTRI WULANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Global climate change cause changing of the rains. Flooding and drought are the effects of climate change. Unpredictable rains cause flooding in cornâs field and reducing yield. The researchâs aims were to determine flooding effects on photosynthesis and cornâs yield. The research also to determine the most important plant growth stage of corn and the cultivar of cornâs tolerant of flooding in some plant growth stages, vegetative with 4 leaves, silking, and milk.. The research had been conducted on June-September 2013 in Tridharma field, Agriculture Department, University of Gadjah Mada, Bantul, D I Yogyakarta. Cornâs cultivars are Bisi 2, Bima 2 Bantimurung, Gumarang, and Srikandi Kuning. The field experiment was arranged in Completely Randomized Block Design (RCBD) factorial with the first factor was cornâs cultivars and the second factor was plant growth stage when flooding occurred. Data of photosynthesis components and yield of corn analyzed by variance analysis and DMRT at Î± = 5%. The result showed that four corn cultivarss, Bisi 2 and Bima 2 Bantimurung that have high potensial yield losses much more than Srikandi Kuning and Gumarang that have less potensial yield when flooding occurred. Flooding causes lost of crop photosynthesis rate and yield in cultivarss that have high potensial yield significantly. Silking is the most important plant growth stage in corn. Bisi 2 is the most tolerant cultivar of flooding that occurred in vegetative with 4 leaves and milk stage.